Weak influence of light and time of day on transcriptional response to SAV3 infection in Atlantic salmon (Salmo salar) smolts - Therese Solberg; Chandra S. Ravuri; Mattis Jayme van Dalum; Jo Espen Tau Strand; David G. Hazlerigg; Eva Stina Edholm; Alexander C. West (Fish & Shellfish Immunology, 2026)

Ocean equity: from assessment to action to improve social equity in ocean governance - Nathan J. Bennett; Veronica Relano; Katina Roumbedakis; Jessica Blythe; Mark Andrachuk; Joachim Claudet; Neil Dawson; David Gill; Natali Lazzari; Shauna L. Mahajan; Ella-Kari Muhl; Maraja Riechers; et al. (Frontiers in Marine Science, 2025)
Inequity is ubiquitous in the ocean, and social equity receives insufficient attention in ocean governance and management efforts. Thus, we assert that proponents of sustainability must center social equity in future ocean governance, to address past social and environmental injustices, to align with international law and conservation policy, and to realize objectives of sustainability. This obligation applies across all marine policy realms, including marine conservation, fisheries management, climate adaptation and the ocean economy, in all socio-political contexts and at different geographical scales. Indeed, many governmental, non-governmental, and philanthropic organizations are striving to advance social equity across their ocean sustainability focused agendas, policies, programs, initiatives, and portfolios. To date, however, there has been limited attention to how to meaningfully assess status and monitor progress on social equity in ocean governance (aka “ocean equity”) across different marine policy realms. Here, we contribute to ongoing efforts to advance ocean equity through providing guidance on five steps to develop bespoke, fit to purpose and contextually appropriate assessment and monitoring frameworks and approaches to measure status of and track changes in ocean equity. These steps include: 1) Clearly articulating the overarching purpose and aim; 2) Convening a participatory group and process to co-design the assessment framework; 3) Identifying important objectives, aspects and attributes of social equity to assess; 4) Selecting and developing indicators, methods, and measures; and 5) Collecting, analyzing and evaluating data. Then, we discuss four subsequent steps to take into account to ensure that assessments lead to adaptations or transformations to improve ocean equity. These steps include: 1) Communicating results to reach key audiences, to enable learning and inform decision-making; 2) Deliberating on actions and selecting interventions to improve ocean equity; 3) Ensuring actions to improve ocean equity are implemented; and, 4) Committing to continual cycles of monitoring, evaluation, learning and adapting at regular intervals. Following these steps could contribute to a change in how oceans are governed. The diligent pursuit of ocean equity will help to ensure that the course towards a sustainable ocean is more representative, inclusive and just.

Physiological trade-offs in male social insects: Interactions among infection, immunity, fertility, size, and age in honey bee drones - Bradley N. Metz; Tatiana Molina-Marciales; Micheline K. Strand; Olav Rueppell; David R. Tarpy; Esmaeil Amiri (Journal of Insect Physiology, 2024)

Arthropod diversity in constructed wetlands is affected strongly by shoreline properties but only weakly by grazing - David Åhlén; Jerker Jarsjö; Mats Jonsell; Björn K. Klatt; Lea D. Schneider; John Strand; Peter A. Hambäck (Journal of Biogeography, 2024)
Aim Aquatic‐terrestrial transition zones contain features essential for many species that often benefit wetland biodiversity. Shallow flood‐zone areas and reed beds are indicative of natural wetland habitats; however, how such features affect the native arthropod biodiversity in constructed wetlands is scarcely investigated. We asked how these shoreline features, as well as wetland shoreline properties and grazing management, influence riparian arthropod diversities and habitat specializations. Location Constructed wetlands, Sweden. Taxa Araneae, Coleoptera, Diptera. Methods Taxonomic‐, phylogenetic‐ and trait diversities, along with habitat specialist species richness, were measured in riparian spiders, beetles and selected Diptera in 68 constructed wetlands in two regions of Sweden. We ran structural equation models to estimate direct and indirect effects from shoreline slope, flooded grassland, reed areas and grazing management on group diversities, and used multivariate models to determine drivers on habitat specialist species richness. Results Flooded grassland and reed area, along with shoreline slope influenced arthropod diversities, and responses differed between arthropod groups and diversity metrics. Spider trait diversity was greater in wetlands with larger flooded grassland areas, whilst beetle trait diversity was reduced. Spider phylogenetic diversity was greater in wetlands containing larger reed areas and in wetlands with steeper shorelines. However, species richness in predatory flies was greater in wetlands with more gentle shorelines. Grazing management had limited effects on arthropod diversities; however, species richness in wetland specialist and generalist predatory dipterans was greater in the absence of grazers in wetlands with greater flooded grassland areas. Main Conclusions As requirements vary considerably among arthropods, care must be taken when constructing and managing wetlands to benefit arthropod biodiversity. The present results suggest wetlands with a varied shoreline, albeit with greater proportions of flood areas, or multiple adjacent wetlands with varying shores in a wet landscape and a mild grazing regiment, would accommodate a more diverse arthropod fauna.

Reflections on the past, present, and potential futures of knowledge hierarchies in ocean biodiversity governance research - Holly J. Niner; David Wilson; Kelly Hoareau; Mia Strand; Jennifer Whittingham; Dylan McGarry; Bolanle Erinosho; Sulley Ibrahim; Sirkka Tshiningayamwe; Senia Febrica; Alana Malinde S. N. Lancaster; Milica Prokic (Frontiers in Marine Science, 2024)
Governance of the ocean and its biodiversity is deeply entangled within social, political and cultural histories. The evolution of marine science has been subject to similar influences, and we (the authors) consider these factors to create, embed and reinforce knowledge hierarchies in ocean governance processes and associated research that set societal patterns of prioritisation and exclusion. Such knowledge hierarchies have constructed dominant Western-oriented knowledge systems as ‘rational’ and ‘objective’ approaches to environmental governance in contrast to non-Western knowledge systems and have led to a dominance of natural (normal) sciences over centralised biodiversity governance. The extraction and incorporation of traditional knowledge into the Western-oriented scientific canon through myriad historical and contemporary processes in ocean biodiversity governance often reproduce knowledge hierarchies, do not benefit knowledge holders and are often considered incomplete, inappropriate or absent. As we address current ocean biodiversity and conservation challenges, researchers must be aware of the history of knowledge extraction, impositions and assumptions within their fields. Researchers must also actively acknowledge and address these histories in their work to avoid marginalisation and support ethical, empathetic, and rigorous knowledge production that meets the needs of society. In this paper, through a development of the concept of knowledge hierarchies, we explore case studies of research diverse in geography and discipline ranging from action research in Namibia, the application of arts-based methodologies in legal proceedings to research focused at an international level, and the concept of ocean literacies, all of which are located under the umbrella of a project specifically targeting transformative ocean governance. It becomes evident that knowledge hierarchies are multi-layered, perpetuating, and often reproduced even when attempting to address hierarchies through such methods as the integration or ‘bringing together’ of diverse knowledge systems. Effective change will therefore require sensitive and multi-faceted approaches to knowledge hierarchies, including processes of embracing discomfort, which will be important to work with, as well as through. While there will be continued tensions between hierarchies, it is a sine qua non that researchers need to build a commitment to understanding where powers lie, rather than ignoring such imbalances or, similarly, by idealising approaches.

Tracking rapid ice recession in a major Southern Alps valley during the last glacial termination - Peter D. Strand; Aaron E. Putnam; Joerg M. Schaefer; George H. Denton; David J.A. Barrell (Quaternary Science Reviews, 2024)

Microcystin profiles in European noble crayfish Astacus astacus and water in Lake Steinsfjorden, Norway - Christopher O. Miles; David A. Strand; Johannes C. Rusch; Andreas Ballot; Sigrid Haande; Kjersti L.E. Løvberg; Trude Vrålstad; Ingunn A. Samdal (Environmental Research, 2024)

Molecular detection of Aphanomyces astaci – An improved species specific qPCR assay - David A. Strand; Tomas Jinnerot; Anna Aspán; Satu Viljamaa-Dirks; Sirpa Heinikainen; Elin Rolén; Trude Vrålstad (Journal of Invertebrate Pathology, 2023)

Latitudinally distinct stocks of Atlantic cod face fundamentally different biophysical challenges under on‐going climate change - Olav Sigurd Kjesbu; Maud Alix; Anne Britt Sandø; Espen Strand; Peter J. Wright; David G. Johns; Anders Thorsen; C. Tara Marshall; Kjell Gunnar Bakkeplass; Frode B. Vikebø; Mari Skuggedal Myksvoll; Geir Ottersen; et al. (Fish and Fisheries, 2023)
The reproductive success of marine ectotherms is especially vulnerable in warming oceans due to alterations in adult physiology, as well as embryonic and larval survival prospects. These vital responses may, however, differ considerably across the species' geographical distribution. Here we investigated the life history, focusing on reproductive ecology, of three spatially distant populations (stocks) of Atlantic cod ( Gadus morhua , Gadidae) (50–80° N), in the Irish/Celtic Seas‐English Channel Complex, North and Barents Seas, under past and projected climate. First, experimental tracking of spawning behaviour evidenced that the ovulation cycle is highly distressed at ≥9.6 (±0.25)°C ( T up ). This knife‐edge threshold resulted in erratic spawning frequencies, whereas vitellogenin sequestration remained unaffected, indicating endocrine rather than aerobic scope constraints. Cod in the Celtic Sea‐English Channel are, therefore, expected to show critical stock depensation over the next decades as spawning grounds warm above T up , with Irish Sea cod subsequently at risk. Second, in the relatively cooler North Sea, the northward retraction of Calanus finmarchicus (Calanidae) and Para‐Pseudocalanus spp. (Clausocalanidae) (1958–2017) limit cod larvae feeding opportunities, particularly in the southernmost subarea. However, the contrasting increase in Calanus helgolandicus (Calanidae) does not counteract this negative effect, likely because cod larvae hatch ahead of its abundance peaks. Overfishing again comes as a twin effect. Third, in the still relatively cold Barents Sea, the sustainably harvested cod benefit from improved food conditions in the recent ice‐free polar region but at the energetic cost of lengthier and faster spawning migrations. Consequently, under climate change local stocks are stressed by different mechanistic factors of varying management severity.

qPCR screening for Yersinia ruckeri clonal complex 1 against a background of putatively avirulent strains in Norwegian aquaculture - Andreas Riborg; Snorre Gulla; David Strand; Jannicke Wiik‐Nielsen; Anita Rønneseth; Timothy J. Welch; Bjørn Spilsberg; Duncan J. Colquhoun (Journal of Fish Diseases, 2022)
Although a number of genetically diverse Yersinia ruckeri strains are present in Norwegian aquaculture environments, most if not all outbreaks of yersiniosis in Atlantic salmon in Norway are associated with a single specific genetic lineage of serotype O1, termed clonal complex 1. To investigate the presence and spread of virulent and putatively avirulent strains in Norwegian salmon farms, PCR assays specific for Y. ruckeri (species level) and Y. ruckeri clonal complex 1 were developed. Following extensive screening of water and biofilm, the widespread prevalence of putatively avirulent Y. ruckeri strains was confirmed in freshwater salmon hatcheries, while Y. ruckeri clonal complex 1 was found in fewer farms. The formalin‐killed bacterin yersiniosis vaccine was detected in environmental samples by both PCR assays for several weeks post‐vaccination. It is thus important to interpret results from recently vaccinated fish with great care. Moreover, field studies and laboratory trials confirmed that stressful management procedures may result in increased shedding of Y. ruckeri by sub‐clinically infected fish. Analysis of sea water sampled throughout thermal delousing procedures proved effective for detection of Y. ruckeri in sub‐clinically infected populations.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

On the Misidentification of Species: Sampling Error in Primates and Other Mammals Using Geometric Morphometrics in More Than 4000 Individuals - Andrea Cardini; Sarah Elton; Kris Kovarovic; Una Strand Viđarsdóttir; P. David Polly (Evolutionary Biology, 2021)

Exploring the international trade in African snakes not listed on CITES: highlighting the role of the internet and social media - Timm Juul Jensen; Mark Auliya; Neil David Burgess; Patrick Welby Aust; Cino Pertoldi; Julie Strand (Biodiversity and Conservation, 2019)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Photoperiod revisited: is there a critical day length for triggering a complete parr–smolt transformation in Atlantic salmon Salmo salar ? - Jo E. T. Strand; David Hazlerigg; Even H. Jørgensen (Journal of Fish Biology, 2018)
The present study investigated whether there is a critical length of photoperiod needed to stimulate a completed parr–smolt transformation (PST) in Atlantic salmon Salmo salar . In two experiments, S. salar parr of the Norwegian aquaculture strain held on continuous light were exposed to a short photoperiod (6 L:18D) followed by exposure to 8 L:16D, 12 L:12D, 16 L:8D, 20 L:4D and 24 L:0D in experiment 1 or to 6 L:18D followed by maintenance on 6 L:18D or exposure to 12 L:12D and 24 L:0D photoperiods in experiment 2. All groups, irrespective of photoperiod treatment, developed improved hypo‐osmoregulatory ability. However, the development was greatest in the groups exposed to 20 L:4D and 24 L:0D in experiment 1 and 24 L:0D in experiment 2. In experiment 2, gill Na + – K + ‐ATPase activity increased in the group exposed to 24 L:0D, but not in the groups exposed to 12 L:12D and 6 L:18D. The groups exposed to 20 L:4D and 24 L:0D in experiment 1 and 24 L:0D in experiment 2 also grew better than fish exposed to shorter photoperiods. In experiment 2 only the group exposed to 24 L:0D showed a decrease in condition factor and increases in plasma growth hormone and brain type 2 deiodinase mRNA abundance. Hence, only the groups exposed to photoperiods above 16 L:8D developed classical smolt indices in the present experiment, leading us to conclude that the photoperiod increase needs to exceed 16 h daylight for stimulating a complete PST in the S. salar used in the present study.

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

eDNA-based crayfish plague monitoring is superior to conventional trap-based assessments in year-round detection probability - Claudia Wittwer; Stefan Stoll; David Strand; Trude Vrålstad; Carsten Nowak; Marco Thines (Hydrobiologia, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Invasion of novel habitats uncouples haplo‐diplontic life cycles - Stacy A. Krueger‐Hadfield; Nicole M. Kollars; James E. Byers; Thomas W. Greig; Mareike Hammann; David C. Murray; Courtney J. Murren; Allan E. Strand; Ryuta Terada; Florian Weinberger; Erik E. Sotka (Molecular Ecology, 2016)
Baker's Law predicts uniparental reproduction will facilitate colonization success in novel habitats. While evidence supports this prediction among colonizing plants and animals, few studies have investigated shifts in reproductive mode in haplo‐diplontic species in which both prolonged haploid and diploid stages separate meiosis and fertilization in time and space. Due to this separation, asexual reproduction can yield the dominance of one of the ploidy stages in colonizing populations. We tested for shifts in ploidy and reproductive mode across native and introduced populations of the red seaweed Gracilaria vermiculophylla . Native populations in the northwest Pacific Ocean were nearly always attached by holdfasts to hard substrata and, as is characteristic of the genus, haploid–diploid ratios were slightly diploid‐biased. In contrast, along North American and European coastlines, introduced populations nearly always floated atop soft‐sediment mudflats and were overwhelmingly dominated by diploid thalli without holdfasts. Introduced populations exhibited population genetic signals consistent with extensive vegetative fragmentation, while native populations did not. Thus, the ecological shift from attached to unattached thalli, ostensibly necessitated by the invasion of soft‐sediment habitats, correlated with shifts from sexual to asexual reproduction and slight to strong diploid bias. We extend Baker's Law by predicting other colonizing haplo‐diplontic species will show similar increases in asexuality that correlate with the dominance of one ploidy stage. Labile mating systems likely facilitate colonization success and subsequent range expansion, but for haplo‐diplontic species, the long‐term eco‐evolutionary impacts will depend on which ploidy stage is lost and the degree to which asexual reproduction is canalized.

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)

Analysis and comparison of the microbial community structures of two enrichment cultures capable of reductively dechlorinating TCE and cis ‐DCE - April Z. Gu; Brian P. Hedlund; James T. Staley; Stuart E. Strand; H. David Stensel (Environmental Microbiology, 2004)
Summary In order to study the effect of different chloroethenes (electron acceptors) on the bacterial composition of dechlorinating communities, two reductive dechlorinating enrichment cultures were developed that were able to reduce trichloroethene (TCE) and cis ‐1,2‐dichloroethene ( cis ‐DCE) to ethene using hydrogen as electron donor, respectively. The inoculum for the cultures was material from a methanogenic fluidized bed reactor (FBR), which was originally seeded with digester sludge and showed a stable capacity for tetrachloroethene (PCE) reduction to ethene for over six years. Molecular methods were used to determine and compare the microbial communities of these two enrichment cultures. A clone library of bacterial 16S rRNA genes was generated for each enrichment. The clones were screened into different groups by restriction fragment length polymorphism (RFLP) analysis using two different four base pair recognition restriction enzymes. A total of 12 sequence types were identified by phylogenetic analysis of nearly complete 16S rDNA sequences (∼1450 bp). The sequences were affiliated with six recognized phyla of the domain Bacteria: Firmicutes (low G+C Gram‐positives), Chloroflexi (green non‐sulphur bacteria), Actinobacteria (high G+C Gram‐positives), Bacteroidetes (Cytophaga‐Flexibacter‐Bacteroides), Nitrospira and Spirochaetes. The results led to the identification of an organism closely related to Dehalococcoides ethenogenes to be the presumptive dechlorinator in both enrichments. Different electron acceptors affected the bacterial diversity and the community profiles of the two enrichments. Most of the sequences identified in our dechlorinating enrichments shared high similarities with sequences previously obtained from other enriched dechlorinating cultures and chlorinated‐compound‐contaminated sediments or aquifers, suggesting these bacteria may have direct or indirect roles in reductive dechlorination.